THE IMPLEMENTATION OF RADIN INTEN II’S NATIONALISM RESISTANCE VALUES WITHIN LOCAL HISTORY LEARNING - Surandi Surandi; Supardi Supardi; Johan Setiawan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
Abstract: The purposes of this study are to find out: (1) the implementation of Radin Inten II’s resistance nationalism values in the learning process; (2) the obstacles experienced by teachers when implementing Radin Inten II’s resistance nationalism values in the learning process; (3) the efforts made by teachers in overcoming obstacles during the implementation of Radin Inten II’s nationalism values in the learning process. This study used qualitative approach with the type of case study conducted at SMAN 1 Kalianda. Data collection techniques consisted of observation, interviews, and documentary studies. Data analysis techniques used the model of Miles & Huberman consisting of data collection, data reduction, data display, and conclusion. The results show: (1) the implementation of Radin Inten II’s nationalism resistance values in the process of learning local history was carried out by compiling a syllabus and implementing learning plan (RPP) by incorporating local history into Indonesian historical material which was consisted of planning, implementation, and evaluation, (2) the obstacles experienced by teachers included: the ability of teachers during learning process, students’ attitudes, and time constraints, (3) the efforts made by the teacher were taking the initiative to instill the values of nationalism in the resistance of Radin Inten II’s, applying various models, strategies, methods and singing a national song before learning. Abstrak: Tujuan penelitian ini adalah untuk mengetahui: (1) implementasi nilai-nilai nasionalisme perlawanan Radin Inten II dalam proses pembelajaran, (2) kendala yang dialami oleh guru saat implementasi nilai-nilai nasionalisme perlawanan Radin Inten II dalam proses pembelajaran, (3) upaya yang dilakukan guru dalam mengatasi kendala yang dihadapi saat implementasi nilai-nilai nasionalisme perlawanan Radin Inten II dalam proses pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus di SMAN 1 Kalianda. Teknik pengumpulan data terdiri dari observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan model Miles & Huberman yang terdiri dari pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan: (1) implementasi nilai-nilai nasionalisme perlawanan Radin Inten II dalam proses pembelajaran sejarah lokal dilakukan dengan menyusun silabus dan rencana pelaksana pembelajaran (RPP) dengan memasukkan sejarah lokal kedalam materi sejarah Indonesia yang terdiri dari perencanaan, pelaksanaan, dan evaluasi, (2) kendala yang dialami oleh guru diantaranya: kemampuan guru dalam proses pembelajaran, sikap siswa, dan adanya keterbatasan waktu, (3) upaya yang dilakukan oleh guru yaitu berinisiatif menanamkan nilai-nilai nasionalisme dalam perlawanan Radin Inten II, menerapkan berbagai model, strategi, metode dan menyanyikan lagu nasional sebelum pembelajaran.